La vivienda tradicional tuxtleca: patrimonio soslayado - Tondopó Mendoza , Yonalli (Pontificia Universidad Católica del Perú, 2025)
Tuxtla Gutiérrez is the capital city of the state of Chiapas, Mexico. Founded by Dominican friars in 1560, Tuxtla Gutiérrez began as a Zoque Indian village with four major neighborhoods: Santo Domingo, San Jacinto, San Andrés, and San Miguel. For many centuries, this settlement’s mainstay was traditional housing, a prevalent architecture. However, it began to be endangered in the 20th century, as demographic, urban, and economic growth led to its minimization and undervaluation by altering its material, stylistic, and architectural properties. It also changed its use from residential to commercial or mixed use, and in the most severe cases, its total disappearance. This document reviews traditional dwellings considered relevant in the city because they are registered in the National Catalog of Immovable Historical Monuments of the National Coordination of Historical Monuments of the National Institute of Anthropology and History. The intention is to highlight their current situation, which is unfavorable because unfortunately many of them only remain as documentary vestiges, having vanished from the city landscape.

Tuxtla Gutiérrez es la ciudad capital del estado de Chiapas, México. Fundada por frailes dominicos en 1560, Tuxtla Gutiérrez comenzó como un pueblo de indígenas zoque con cuatro barrios principales: Santo Domingo, San Jacinto, San Andrés y San Miguel. Durante muchos siglos, este asentamiento tuvo como elemento fundamental la vivienda tradicional, una arquitectura predominante. Sin embargo, en el siglo XX esta comenzó a peligrar, pues el crecimiento demográfico, urbano y económico propició su minimización e infravaloración al alterar sus propiedades materiales, estilísticas y arquitectónicas; asimismo, al cambiar su uso habitacional por comercial o mixto, y, en los casos más graves, suscitar su desaparición total. Este documento revisa las viviendas tradicionales consideradas relevantes en la ciudad por estar inscritas en el Catálogo Nacional de Monumentos Históricos Inmuebles elaborado por la Coordinación Nacional de Monumentos Históricos, entidad del Instituto Nacional de Antropología e Historia (INAH). La intención es visibilizar su desfavorable situación actual, ya que, lamentablemente, un número significativo de estos inmuebles ha desaparecido del paisaje de la ciudad y se conserva solo como vestigio documental.
Traditional Tuxtla Housing: Overlooked Heritage
Keywords: Traditional housing; Architecture; Material heritage; Heritage loss; Conservation; Vivienda tradicional; Arquitectura; Patrimonio material; Pérdida patrimonial; Conservación; https://purl.org/pe-repo/ocde/ford#6.04.08